2021
DOI: 10.1002/ev.20477
|View full text |Cite
|
Sign up to set email alerts
|

A learning agenda for the advocacy evaluation field's future

Abstract: This volume set out to document, illustrate, and critique the progress and innovation that has occurred during the advocacy evaluation field's first phase of development. This final chapter identifies how the context in which advocacy evaluation plays out is shifting. It describes how these shifts impact how advocates, advocacy funders, and advocacy evaluators think about what works, and what has value. Given this context, and lifting up the ideas of other chapter authors, the chapter concludes with a learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Regarding the practice benefits of SCALE 3D (Research Question 1), the applications of SCALE 3D confirm and complement reported benefits previously identified (Strasser et al, 2020(Strasser et al, , 2022 and suggest that SCALE 3D can be useful to support strategic learning (Carr et al, 2019;Coffman and Beer, 2011) specifically for TSI networks. Our findings align with potential benefits of using a ToC for strategy and evaluation (Dhillon and Vaca, 2018), including more coherent and aligned interventions, mutual understanding among staff, communication with funders, explicitly articulated assumptions, more intentional execution and learning and better and timely decisions when adapting to emerging issues.…”
Section: Potential Advantages Of Applying Scale 3dsupporting
confidence: 72%
See 1 more Smart Citation
“…Regarding the practice benefits of SCALE 3D (Research Question 1), the applications of SCALE 3D confirm and complement reported benefits previously identified (Strasser et al, 2020(Strasser et al, , 2022 and suggest that SCALE 3D can be useful to support strategic learning (Carr et al, 2019;Coffman and Beer, 2011) specifically for TSI networks. Our findings align with potential benefits of using a ToC for strategy and evaluation (Dhillon and Vaca, 2018), including more coherent and aligned interventions, mutual understanding among staff, communication with funders, explicitly articulated assumptions, more intentional execution and learning and better and timely decisions when adapting to emerging issues.…”
Section: Potential Advantages Of Applying Scale 3dsupporting
confidence: 72%
“…] Innovators are accountable to the learning' (Preskill and Beer, 2012: 16). Through 'strategic learning', evaluation and strategy interact in a reciprocal relationship (Carr et al, 2019;Coffman and Beer, 2011;Preskill and Mack, 2013): The strategic orientation of vision, mission and goals informs what is relevant to measure, while the reflection on data, assumptions and evidence can help to guide strategic thinking and to make better decisions in uncertain and emergent circumstances (Coffman and Beer, 2011).…”
Section: The Challenge Of Evaluating Social Innovation For Transforma...mentioning
confidence: 99%
“…The advocacy work included capacity building, sensitisation and awareness creation; strategic communications, media advocacy and policy advocacy. The framework that undergirded the advocacy intervention was developed by Coffman and Beer 25. Our chosen strategies were informed by our target audiences (public, influencers and decision-makers)—see figure 2.…”
Section: The Strategies and Approaches We Usedmentioning
confidence: 99%
“…The framework that undergirded the advocacy intervention was developed by Coffman and Beer. 25 Our chosen strategies were informed by our target audiences (public, influencers and decision-makers)—see figure 2 .…”
Section: The Strategies and Approaches We Usedmentioning
confidence: 99%
“…Based on existing literature, three main reasons for the low-level of advocacy evaluation by NGOs can be identified. First, NGOs have limited human and financial resources devoted to evaluation (Coffman, 2009; Jones, 2011). Second, advocacy organizations are hesitant to conduct and share evaluations due to fear of revealing strategies, which could benefit competing organizations or those to be influenced (Patton, 2008).…”
Section: Introductionmentioning
confidence: 99%